An investigation study on the implementation of material wastage management in construction site of residential housing and highrise building / Muhammad Khidir Abd Rahman - Abd Rahman, Muhammad Khidir (2015)
Material management is one of the activities in construction that need some particular skills or technique for achieving best performance in construction. It is also as an important part in construction management in order to reduce waste material on site during construction works. Poor material management on construction site will cause problem to construction such that effect to finance, budgeting and environment. The study is all about material management on construction site during construction work. The aim of this research is to establish the sustainable practice of material management on construction site. The study will be done by comparing between two different construction type which that construction of housing project at Sungkai and Ipoh, Perak and construction of high rise building at Kota Bharu, Kelantan and Taiping, Perak. This two type of construction project have there own material management because it has difference size of construction site and different on material used. Therefore, this study will be done by using quantitative data to receive any perspective from workers that responsible on construction work at housing project. The result from this paper will determine the employee’s perspective for material management from two different types of construction project and this paper can be used for future study. Factor to be considered on material management can give some opportunities to construction industry to provide best practise on material managing during construction work in order to reduce cost of project.